2022
DOI: 10.1108/tlo-01-2021-0018
|View full text |Cite
|
Sign up to set email alerts
|

Learning from the future as a novel paradigm for integrating organizational learning and innovation

Abstract: Purpose The purpose of this paper is to challenge processes of organizational learning and innovation that are based on making use of, extrapolating, or adapting past experiences and knowledge, because such a strategy turns out to be incapable of dealing with the challenges of today’s volatile, uncertain, complex and ambiguous environment. As a possible way out, a conceptual model is proposed that integrates organizational learning and innovation as a future-driven learning process and a future-making practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The answer might lie in new processes and capabilities, as suggested by Peschl (2022). He suggests looking at future possibilities and opportunities by engaging in scenario planning.…”
Section: Learning From the Futurementioning
confidence: 99%
See 2 more Smart Citations
“…The answer might lie in new processes and capabilities, as suggested by Peschl (2022). He suggests looking at future possibilities and opportunities by engaging in scenario planning.…”
Section: Learning From the Futurementioning
confidence: 99%
“…In this way, the scenarios that are developed can provide different perspectives on the future that can form the basis for further action, as well as dialog and learning. In this way, practitioners should abandon the practice of predicting and controlling the present and future and accept the approach of “learning from the future” (Peschl, 2022) and actively shaping it. In this way, the organization and its members discover something latent that is still emerging or not yet realized, in short, it is “not yet.”…”
Section: Learning From the Futurementioning
confidence: 99%
See 1 more Smart Citation
“…Scharmer, 2009). Learning from the future has been studied by various researchers in recent years (Peschl, 2022), (Peschl, 2019), (C. O. Scharmer, 2009), (Grisold, Kaiser, & Hafner, 2017), (Kaiser, Kragulj, Grisold, & Walser, 2016), , and all these authors have shown that self-transcending knowledge plays an important role.…”
Section: Types Of Knowledgementioning
confidence: 99%
“…Agility and utilization of emerging informational technologies are defined as effective strategies for navigating the challenges, posed by the VUCA world. According to Peschl (2023), events of the VUCA environment are the triggers for learning and (radical) transformations that are necessary for organizational success. Therefore, he poses, it is "not sufficient to have only well-established stimulus-response patterns/routines in place".…”
Section: It Adaptability Organizational Performance and Vuca Environmentmentioning
confidence: 99%